When religion becomes an obstacle to the inclusion of sexual and gender dissidents in the school space - Espejo, Juan Cornejo (Education Policy Analysis Archives, 2021)
The purpose of the article is to analyze the integration processes of sexual and gender dissident students in religious educational establishments of different administrative dependencies in five regions of central-southern Chile. From the methodological point of view, the research ascribes to a qualitative approach, based on a descriptive-interpretive study carried out through semi-structured interviews applied to different educational agents from 12 establishments during the year 2019. Among the main findings is the tension implied by the presence of dissidents, whose integration fluctuates between silencing and denial depending on the religious orientation of the establishment. In this context, Catholic establishments tend to welcome dissidents as long as they remain in the closet, those who resist become “problem students.” Evangelical schools are characterized by their intransigence, with repetitive sermons about the abomination of a dissident orientation and / or identity. Adventist establishments, even if not as frontal, are very active in their religious indoctrination programs, whose purpose is to discourage any possible dissent. The Mormon establishment, for its part, tends to evade the issue, denying the possibility that there may be dissenters among its students.